Standing Intraoral Extraction of the Right Mandibular Third Molar Tooth in a Cow Utilizing Tooth Sectioning. (March 2022) - Amitrano, Fernando N.; Shaw, Kelly; De Gasperi, Diego; Henry, Travis; Brounts, Sabrina H.
A 2-year-old Holstein heifer presented to a university teaching hospital with an apical tooth infection of the right mandibular third molar. A standing oral extraction technique was attempted for tooth removal; however, the molar could not be delivered intact. A tooth sectioning technique was performed, and the affected molar was successfully delivered. Three months postextraction, the heifer had fully recovered, and the extraction site had healed. To the authors' knowledge, this is the first description of a tooth extraction in a cow using a tooth sectioning technique. This case describes an alternative technique for tooth removal in cattle with an apical tooth infection. The clinical, diagnostic, and therapeutic features of this case may be helpful to clinicians when they approach similar cases in the future.